TINJAUAN ATAS PROSEDUR PROCUREMENT TO PAY PADA DI LINGKUNGAN CONTRACT AND PROCUREMENT PADA BIDANG MATERIAL DI PT CHANDRA ASRI PETROCHEMICAL TBK - Moza Salma (2020)
Companies surely done procurement to fulfill what the companies needs. The purpose of this thesis is to knowing and understanding the procurement system and understanding role of the related department while in procurement to pay process. Contract and Procurement Department in PT Chandra Asri Petrochemical Tbk. perform the procurement as main tasks and the function is corresponding to company regulations. In purchase procedure, when procurement is performed related functions and documents is used to support the purchase procedure. Procurement procedure begins from goods demand using Purchase Requisition document and the process is using the Technical Evaluation, Commercial Evaluation, Contract and Co- ordination Meeting and Request for Quotation documents until the process is became Purchase Order that sent to vendor. Before payment is performed, Warehouse Department receive goods and the documents then verify arrived goods which was requested. The payment is done through bank transfer that paid by Finance Department after all transactions is posted by Accounting Department. According to writer analysis, the procurement procedure that performed at PT Chandra Asri Petrochemical Tbk. is already appropriate with the standard regulations.